Vliv odluky na financování církví - Zeitham, Libor (Univerzita Karlova, Husitská teologická fakulta, 2020)
Abstarakt - English This thesis analyses current state of churches financing. Following implementation of the Act of Property Settlement with churches and religious societies, the churches receive state contribution intended for churches' service reduced by 5 per cent from the original compensation amount every year since 2016. The contribution shall be paid out till final termination in 2027. Moreover, according to the Act, churches receive financial compensation for thirty years since 2013. This thesis asks following question: Could the churches be able (after thirty years) to finance their services from the state financial compensation only which they would regularly invest during the thirty years and from which only salaries should be paid in the anticipated level of 2013 valorized since 2019 by supposed inflation. The state financial compensation is supposed to be valorized by the same inflation. The calculations resulted in finding that only the Roman-Catholic Church would prove to be succesfull under given conditions. Due to the fact that churches do not invest the whole state contribution/subsidy excluding salaries (which was the necessary pre-requisite) neither the Roman-Catholic Church would succeed. It doesn't mean that the churches will terminate their activities by that time but structure of. Práce se zabývá analýzou současného stavu financování církví. Církve po schválení zákona o majetkovém vyrovnání s církvemi a náboženskými společnostmi pobírají příspěvek od státu na provoz církví, který se od roku 2016 snižuje ročně o pět procent z původní vyplácené částky ročně. Příspěvek bude vyplácen až do roku 2029, kdy bude vyplácení ukončeno. Dále ze zákona je církvím vyplácena finanční náhrada od roku 2013 po dobu třiceti let. Otázka, kterou řešila tato práce zněla: Zda jsou církve po třiceti letech schopny se sami financovat pouze z prostředků od státu, které by v průběhu těchto třiceti let pravidelně investovaly a platily by z nich pouze mzdy v předpokládané výši příspěvku na provoz z roku 2013 a ...